Arthroscopic-Assisted Combined Dorsal and Volar Scapholunate Ligament Reconstruction with Tendon Graft for Chronic SL Instability - Ho, Pak-cheong; Wong, Clara Wing-yee; Tse, Wing-lim (Journal of Wrist Surgery, 2015)
Background Both the dorsal and the volar portion of the scapholunate interosseous ligament (SLIL) are major stabilizers of the scapholunate (SL) joint. Most reconstruction methods to restore SL stability do not address the volar constraints and frequently fail to reduce the SL gapping. Wrist arthroscopy allows a complete evaluation of the SL interval, accompanying ligament status, and associated SL advanced collapse (SLAC) wrist changes. It enables simultaneous reconstruction of the dorsal and palmar SL ligaments anatomically with the use tendon graft in a boxlike structure.Materials and Methods From October 2002 to June 2012, the treatment method was applied in 17 patients of chronic SL instability of average duration of 9.5 months (range 1.5–18 months). There were three Geissler grade 3 and 14 grade 4 instability cases. The average preoperative SL interval was 4.9 mm (range 3–9 mm). Dorsal intercalated segment instability (DISI) deformity was present in 13 patients. Six patients had stage 1 SLAC wrist change radiologically. Concomitant procedures were performed in four patients.Description of Technique With the assistance of arthroscopy and intraoperative imaging as a guide, a combined limited dorsal and volar incision exposed the dorsal and palmar SL interval without violating the wrist joint capsule. Bone tunnels of 2.4 mm were made on the proximal scaphoid and lunate. A palmaris longus tendon graft was delivered through the wrist capsule and the bone tunnels to reduce and connect the two bones in a boxlike fashion. Once the joint diastasis is reduced and any DISI malrotation corrected, the tendon graft was knotted and sutured on the dorsal surface of the SL joint extra-capsularly in a shoe-lacing manner. The scaphocapitate joint was transfixed with Kirschner wires (K-wires) to protect the reconstruction for 6–8 weeks.Results The average follow-up was 48.3 months (range 11–132 months). Thirteen returned to their preinjury job level. Eleven patients had no wrist pain, and six had some pain on either maximum exertion or at the extreme of motion. The average total pain score was 1.7/20 compared with the preoperative score of 8.3/20. The postoperative average total wrist performance score was 37.8/40, with an improvement of 35%. The average extension range improved for 13%, flexion range 16%, radial deviation 13%, and ulnar deviation 27%. Mean grip strength was 32.8 kg (120% of the preoperative status, 84% of the contralateral side). The average SL interval was 2.9 mm (range 1.6–5.5 mm). Recurrence of a DISI deformity was noted in four patients without symptoms. Ischemic change of proximal scaphoid was noted in one case without symptoms or progression. There were no major complications. All patients were satisfied with the procedure and outcome.Conclusion Our method of reconstructing both the dorsal and volar SL ligament, in a minimally invasive way, is a logical and effective technique to improve SL stability. The potential risk of ischemic necrosis of the carpal bone is minimized by preservation of the scaphoid blood supply, the small size of the bone tunnels created, and the inclusion of the capsule at the reconstruction site.
Keywords: wrist arthroscopy; scapholunate ligament; SL dissociation; wrist surgery; tendon graft